Development of water-soluble polyanionic carbosilane dendrimers as novel and highly potent topical anti-HIV-2 microbicides. Issue 35 (14th August 2015) - Briz, Verónica; Sepúlveda-Crespo, Daniel; Diniz, Ana Rita; Borrego, Pedro; Rodes, Berta; de la Mata, Francisco Javier; Gómez, Rafael; Taveira, Nuno; Muñoz-Fernández, Mª Ángeles
Abstract : Polyanionic carbosilane dendrimers inhibit HIV-2 binding, inactivate the virus, block cell-to-cell fusion, and enhance the antiviral activity combined with tenofovir/raltegravir. Abstract : The development of topical microbicide formulations for vaginal delivery to prevent HIV-2 sexual transmission is urgently needed. Second- and third-generation polyanionic carbosilane dendrimers with a silicon atom core and 16 sulfonate (G2-S16), napthylsulfonate (G2-NS16) and sulphate (G3-Sh16) end-groups have shown potent and broad-spectrum anti-HIV-1 activity. However, their antiviral activity against HIV-2 and mode of action have not been probed. Cytotoxicity, anti-HIV-2, anti-sperm and antimicrobial activities of dendrimers were determined. Analysis of combined effects of triple combinations with tenofovir and raltegravir was performed by using CalcuSyn software. We also assessed the mode of antiviral action on the inhibition of HIV-2 infection through a panel of different in vitro antiviral assays: attachment, internalization in PBMCs, inactivation and cell-based fusion. Vaginal irritation and histological analysis in female BALB/c mice were evaluated. Our results suggest that G2-S16, G2-NS16 and G3-Sh16 exert anti-HIV-2 activity at an early stage of viral replication inactivating the virus, inhibiting cell-to-cell HIV-2 transmission, and blocking the binding of gp120 to CD4, and the HIV-2 entry. Triple combinations with tenofovir and raltegravir increased the anti-HIV-2 activity, consistent with synergistic interactions (CIwt : 0.33–0.66). No vaginal irritation was detected in BALB/c mice after two consecutive applications for 2 days with 3% G2-S16. Our results have clearly shown that G2-S16, G2-NS16 and G3-Sh16 have high potency against HIV-2 infection. The modes of action confirm their multifactorial and non-specific ability, suggesting that these dendrimers deserve further studies as potential candidate microbicides to prevent vaginal/rectal HIV-1/HIV-2 transmission in humans.